TRAINING ON MAKING FUNCTIONAL FOOD PRODUCTS BASED ON GLUTINOUS CORN FLOUR - Tagor M. Siregar; Julia Wijaya; Natania Natania; Titri Siratantri; Florecita Sanaky; Evelyn Chen; Keshia Wela (Community Development Journal : Jurnal Pengabdian Masyarakat, 2025)
The Women Farmers Group (KWT) Forum in Tangerang Selatan is a community group that engages in cultivating spices and other food crops like chilies, cauliflower, tomatoes, cucumbers, Pok Choy, and red spinach. Since the beginning of 2023, the Tangerang Selatan KWT Forum has been cultivating glutinous corn, which is a food crop with the potential to provide health benefits and added economic value for the community. The Tangerang Selatan KWT Forum has limited knowledge about the health benefits and how to process glutinous corn plants into functional food products. Community Service Activities (PkM) of the UPH Food Technology Study Program in the form of training in making functional food products based on glutinous corn flour can be a solution to overcome this condition. This training activity is carried out through the preparation and implementation stages. In the preparation stage, a trial process was conducted to determine the best preparation procedure and formulation for the instant glutinous corn soup product at the Food Processing Laboratory of the UPH Food Technology Study Program. The final preparation stage consists of preparing a training video. The training was conducted on September 21 2023 and was attended by 35 participants. The results of the evaluation of the implementation of training activities based on filling out questionnaires showed that all (100%) participants stated that this activity was well attended, useful, and very interesting. As a result of the training, making instant glutinous corn soup can become an alternative daily activity for members of the KWT Forum in Tangerang Selatan, providing health and economic benefits for the community.